Phonological awareness in German-speaking preschool children with cochlear implants – 3 case examples. (September 2017) - Wachtlin, Bianka; Turinsky, Yvonne; Herrmann, Frank; Schaefer, Blanca
Abstract: Objective: The aim was to explore PA skills German-speaking preschool children with cochlea implants (CIs) and how these skills may be related to their speech and language skills. Methods: Three monolingual German-speaking pre-school children aged 5;04–6;01 with bilateral CIs were tested. Their cognitive, speech and language skills were assessed. Six subtests of a standardized PA test battery were administered (i.e. rhyme identification, rhyme production; phoneme identification- input and -output; phoneme blending-input and -output). Results: All three children showed distinctive PA profiles. One boy, who had no spoken language deficits, struggled to complete the rhyme tasks but performed well on three phoneme tasks. However, he showed a discrepancy between expressive and receptive phoneme blending skills, scoring poorly on the expressive subtest. The second boy, who displayed grammar comprehension and expressive vocabulary difficulties, showed a mixed profile, with a below average performance on rhyme production. The girl who had significant speech and language deficits scored below average on all six PA subtests. Conclusions: PA profiles in children with CI vary considerably and PA testing should include a range of different PA tasks. The assumed link between spoken language deficits and PA difficulties shown in children with normal hearing could be confirmed.